Topical and systemic anticholinergic for treating hyperhidrosis - de Almeida, Ada Regina Trindade; de Moura Moreira, Vanessa Rocha; Ferrari, Fernanda (Shanghai Chest; Vol 3 (August 2019): Shanghai Chest, 2019)
Topical and systemic anticholinergic drugs continue to be useful medications in the management of Hyperhidrosis and accordingly to the International Hyperhidrosis Society (IHHS) algorithm for treatment, they are the initial therapeutic option for all primary forms of excessive sweating. In this article, several topical and systemic agents will be reviewed and information about efficacy, safety and side effects will be discussed.